Spawned with a silver spoon? Entrepreneurial performance and innovation in the medical device industry - Chatterji, Aaron K. (Strategic Management Journal, 2009)
Abstract Entrepreneurs in high‐technology industries often have prior experience at incumbent firms, but we know little about how knowledge obtained at the prior employer impacts entrepreneurial performance. Drawing on previous work from strategy, economics, and organizational sociology, I assess the impact of industry experience on entrepreneurial performance and innovation in medical device start‐ups. I find that spawns (ventures started by former employees of incumbent firms) perform better than other new entrants. Interestingly, my findings suggest that this superior performance is not driven by technological spillovers from parent to spawn, but rather by nontechnical knowledge related to regulatory strategy and marketing. Copyright © 2008 John Wiley & Sons, Ltd.